Lamotrigine for trigeminal neuralgia: Efficacy and safety in comparison with carbamazepine - Shaikh, S.; Hashim, Y.; Rusdi, A.R. (2011)
Background: Anticonvulsants are regarded as useful for the treatment of neuropathic pain. In this study, we evaluated the efficacy and occurrence of side effects of lamotrigine (LTG) in comparison with carbamazepine (CBZ), in trigeminal neuralgia (TN) patients. Methods: The study was an interventional and crossover comparison. Twenty-one patients with TN were administered with LTG in comparison to CBZ. The clinical trials comprised two phases of 40 days each, with an intervening three-day washout period. The final titration in dose for LTG was 400 mg and 1,200 mg for CBZ. Efficacy of the medications involved was determined by visual analog scale (VAS) and verbal rating scale (VRS). Side effects were recorded through marking of the profiles of side effects encountered on administration of LTG and CBZ, together with baseline haematological, hepatic and renal investigations. Results: Both on VAS and VRS assessments, in terms of proportion of patients, CBZ benefitted 90.5% (19/21) of the patients with pain relief ( p < 0.05), in contrast to 62% (13/21) from LTG. On VAS assessment, of the 13 patients who gained pain relief from LTG and 19 from CBZ, 77% (10/13) obtained a “complete” degree of pain relief from LTG, as compared with 21% (4/19) from CBZ. On VRS assessment, with LTG, 84% (11/13) of the patients accomplished “much better” degree of pain relief, as compared with 26% (5/19) with CBZ. On LTG, 67% (14/21) of patients endured general pharmacological side effects, as compared with 57% (12/21) of patients on CBZ ( p > 0.05). Meanwhile, LTG inflicted 14% (3/21) of the patients with haematological, hepatic and renal derangements, as compared with 48% (10/21) on CBZ. Conclusion: LTG is generally an effective and safe treatment for management of TN, compared to CBZ